Factors related to work ability and well-being among women on sick leave due to long-term pain in the neck/shoulders and/or back: a cross-sectional study - Mamunur Rashid; Marja-Leena Kristofferzon; Marina Heiden; Annika Nilsson (BMC, 2018)
Abstract Background Musculoskeletal pain is one of the leading causes of sick leave, especially among women, in Western countries. The aim of the present study was to identify factors associated with work ability and well-being, respectively, among women on sick leave due to long-term pain in the neck/shoulders and/or back. Methods A cross-sectional study with a correlational design was conducted on women who were sick-listed due to long-term pain in the neck/shoulders and/or back. A total of 208 participants responded to a survey comprising eight instruments: Multidimensional Pain Inventory scale, General Self-Efficacy scale, Sense of Coherence scale, Coping Strategies Questionnaire, Demand-Control-Support Questionnaire, Hospital Anxiety and Depression Scale, Work Ability Index and Life Satisfaction questionnaire. Multiple linear regression analyses were performed to identify factors associated with work ability and well-being, respectively. Results Women who more strongly believed they would return to the same work had greater work ability (β = 0.39, p < 0.001), whereas women with higher pain intensity (β = − 0.30, p < 0.001) and higher job strain (β = − 0.12, p < 0.05) had lower work ability. Women with higher self-efficacy rated greater well-being (β = 0.14, p < 0.05). As the women's scores for depression increased, their well-being decreased by 48%, which was statistically significant (p < 0.001). The regression models for work ability and well-being were significant (p < 0.001), and their adjusted R- square values were 48% and 59%, respectively. Conclusions The study suggests that the factors beliefs to be back at the same work, pain intensity and job strain are predictive of work ability. Moreover, the factors self-efficacy and depression seem to be predictive of well-being. The findings highlight factors that should be considered by health care professionals and policy-makers to guide attempts to reduce sick leave.